The indirect impact of crop insurance on household food security in the Guinea savannah region of West Africa - Mponela, Powell; Kizito, Fred (2022)
Under high climatic, disease and market uncertainty, smallholder farmers make heuristic decisions on whether to manage risk and invest in profitable alternatives or, as a risk-averse mechanism, continue with the traditional low-risk low-return practices. The goal of this paper is to investigate the role of information, social capital, and resource endowments on farmers' decision to invest in insurance bundled with fertilizer and modern improved seeds and its impacts on food security indicators including surplus produce, marketing share, and produce storage. Results show that insurance induces a 113% increase in the proportion of maize sold and an increased probability to keep food reserves for the lean period by 42%. Impacts of insurance on marketing and storage are contingent on cropping system, agro-advisory and resource endowments with differentiated effects. These findings reveal that bundling crop insurance with high-cost productivity improving inorganic fertilizers and modern improved varieties bred for drought tolerance is a viable option for farmers to make risky productivity-enhancing investments and improve livelihoods that contribute economic development and food security.